2015
DOI: 10.1021/acschembio.5b00004
|View full text |Cite
|
Sign up to set email alerts
|

A Small Molecule That Inhibits OGT Activity in Cells

Abstract: O-GlcNAc transferase (OGT) is an essential mammalian enzyme that regulates numerous cellular processes through the attachment of O-linked N-acetylglucosamine (O-GlcNAc) residues to nuclear and cytoplasmic proteins. Its targets include kinases, phosphatases, transcription factors, histones, and many other intracellular proteins. The biology of O-GlcNAc modification is still not well understood and cell-permeable inhibitors of OGT are needed both as research tools and for validating OGT as a therapeutic target. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

16
211
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 225 publications
(228 citation statements)
references
References 44 publications
16
211
0
1
Order By: Relevance
“…Despite recent progress [10,11], very few such non-substrate-like GT inhibitors are currently available, in stark contrast to other enzyme classes of similar size and biological importance (e.g. kinases, proteases).…”
Section: Introductionmentioning
confidence: 99%
“…Despite recent progress [10,11], very few such non-substrate-like GT inhibitors are currently available, in stark contrast to other enzyme classes of similar size and biological importance (e.g. kinases, proteases).…”
Section: Introductionmentioning
confidence: 99%
“…High‐throughput screening has been pursued to deliver hits that can be improved upon 5b,5d. These leads, however, show modest cellular activity and limited solubility 5b.…”
mentioning
confidence: 99%
“…These leads, however, show modest cellular activity and limited solubility 5b. They also exhibit off‐target cellular toxicity 5b. Another approach5c has been to generate a GlcNAc analogue, 2‐acetamido‐2‐deoxy‐5‐thio‐α‐ d ‐glucopyranose (5SGlcNAc, 3 ), which in its per‐O‐acetylated form (Ac 4 5SGlcNAc, 3 ‐OAc) can diffuse across the plasma membrane.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Because HSV relies on the cellular transcriptional machinery for expression of its genes, we determined if OGT plays a role during HSV infection. To address this question, we utilized a recently developed small molecule inhibitor of OGT, OSMI-1, which was shown to specifically inhibit the catalytic activity of OGT, decrease global O-GlcNAcylation, and inhibit O-GlcNAc modification of known OGT substrates (19). We observed that blocking OGT's catalytic activity significantly decreases replication of HSV-1, HSV-2, and cytomegalovirus.…”
mentioning
confidence: 99%